Phenolic compounds of aqueous and methanol extracts of hypsizygus tessellatus (brown and white var.) and flammulina velutipes caps : antioxidant and antiproliferative activities - Ukaegbu, Chinonso Ishmael; Rashid, Shah Samiur; Hazrulrizawati, Hamid; Alara, Oluwaseun Ruth; Sarker, Zaidul Islam (Springer, 2020)
Since the World Health Organization has suggested the exploration of natural products for cancer management owing to the side effects of chemotherapy and irradiation on humans and breast cancer accounts for the highest number of cancer related deaths globally, this study has examined antiproliferative effects of the aqueous and methanol extracts of Hypsizygus tessellatus (brown and white var.) and Flammulina velutipes caps against two breast cancer cell lines. The antioxidant and antiproliferative activities of these mushroom extracts were evaluated in vitro using chemical-based (for antioxidant activity) and cell (for antiproliferative activity) approaches. Furthermore, the phytochemical composition of the mushroom extracts were identified using mass spectroscopy (UPLC-QTOF/MS). The obtained results showed aqueous extracts of F. velutipes (Enoki) and white H. tessellatus (Bunapi shimeji) caps to possess higher antiodixant activities against DPPH (IC50 = 0.202 and 0.573 mg/mL, respectively), and H2O2 (IC50 = 0.622 and 0.745 mg/mL, respectively) compared tothe methanol extracts. Aqueous extracts of the mushrooms also showed better ferric reducing antioxidant power (FRAP) values against ferric ions compared to the methanol extracts. Finally, the mushroom extracts showed good antiproliferative activities against human breast cancer cell lines. These findings suggest the presence of phytochemicals with antiproliferative and antioxidant acrtivities in the mushroom extracts studied.